Remote Management of Heart Failure: An Overview of Telemonitoring Technologies - Darshan H Brahmbhatt (Radcliffe Medical Media, 2019)
Technological advances have enabled increasingly sophisticated attempts to remotely monitor heart failure. This should allow earlier identification of decompensation, better adherence to lifestyle changes and medication and interventions (such as diuretic dosage changes) that reduce the need for hospitalisation. This review discusses telemonitoring approaches in heart failure, and the evidence for their impact. It is not difficult to collect data remotely, but converting more data into better decision-making that improves the outcome of care is challenging. Policy-makers and technology companies are enthusiastic about the potential of digital technologies to transform healthcare and bring expertise to the patient, rather than the other way round, but guideline writers are not yet convinced, due to the lack of consistent findings in randomised trials.